The Effect of Composite Brushing with Different Types of Toothpaste on Stain Due to Immersion in Coffee, Tea and Cuko Pempek Water - Karin Tika Fitria; Slamet Riyadi (Jurnal Kesehatan Gigi, 2022)
ABSTRACTComposite is a tooth-colored filling material that can change color by extrinsic staining such as coffee, tea and cuko pempek. Abrasive toothpaste can reduce stains but increase surface roughness. This study aims to determine the effect of the type of toothpaste for brushing on the formation of stains caused by coffee, tea and cuko pempek. This research is a quasi-experimental with pre and post control group design. 39 composite discs with a diameter of 1 cm and a thickness of 5 mm were prepared and divided into several groups, 1 group of negative control without treatment, 3 groups of immersion. Each immersion group was divided into 4 brushing groups, namely without brushing, brushing without toothpaste, brushing with abrasive paste and brushing with non-abrasive paste. Pre and post treatment discs were photographed and color changes were assessed using the CIE L*a*b and E system. Friedman, Kruskall Wallis and Mann Whitney U non-parametric analysis test was used to compare color values and color differences within groups and between groups. Based on this study, it can be concluded that there were significant color changes before and after the soaking treatment with coffee, tea and cuko pempek. The color change in coffee was significantly greater than that of tea and cuko pempek. There was no significant difference in color change between tea and cuko pempek. Conclusion: Brushing with toothpaste Keywords: composite; coffee; tea; cuko pempek; CIE LAB